The thirteenth cat : a thriller - Hahn, Mary Downing (Clarion Books, 2021)
Zoey loves staying with her Aunt Alice for the summer, but she doesn't like the creepy house next door with its pack of wild black cats. Then Zoey hears that their neighbor is a witch. Zoey suddenly realizes that there is something strange about the cats. She decides to investigate what is happening inside the house next door and puts herself in grave danger.